A retrospective investigation of the impact of `eventing phase (dressage, show-jumping and cross-country)` on pre-competition anxiety and self-confidence - McGinn, S.; Alcock, D.; Cameron, L. J. (Comparative Exercise Physiology, 2019)
Working in the discipline of eventing (the triathlon of equestrian sport), the present study aims to extend current literature on the use of psychological skills within equestrian sports, by understanding and identifying differences in levels of self-confidence and competitive anxiety. Each eventing phase (dressage, show-jumping and cross-country) was considered and its impact on anxiety and self-confidence analysed. Level of competition was considered a covariate and its effect on specific eventing phases and any associated influence on anxiety and self-confidence within eventing phase was analysed. An experimental, 3×3 factorial, within-subjects design was used. 57 participants (52 female and 5 male; 18 professional, 36 amateur and 3 undefined) completed the Revised Competitive Sport Anxiety Inventory 2 (CSAI-2R), a 17-item questionnaire measuring anxiety and self-confidence. Descriptive statistics identified the show-jumping phase had the largest impact on rider somatic anxiety (SA) and cognitive anxiety (CA). The cross-country phase had the highest self-confidence mean score. Spearman`s rank correlations showed both SA and CA were debilitative for all competition levels. Both SA and CA were found to be more debilitating in the show-jumping phase when self-confidence was low. MANCOVA analysis showed that eventing phase had significant effect on anxiety and self-confidence when controlling for level of competition. Dependent on the eventing phase riders are competing in, they experience different levels of arousal and self-confidence. When SA and CA are a debilitative source of anxiety, this could result in rider muscle tension which is not conducive to effective horse-rider communication. Coaches or sports psychologists should consider how to help riders manage their anxiety levels in relation to the competition phase, with the intention of enhancing self-confidence and enabling facilitative SA and CA in preparation for eventing performance